Regional Human Resource Development in ASEAN: An Institutional Theory Perspective - Oleksandr, Tkachenko; Oliver, Crocco; Loi, Nguyen; Victoria, Jonathan (Sage, 2022)
With the growing influence of intergovernmental organizations such as the European Union and the Association of Southeast Asian Nations (ASEAN), the scope and complexity of human resource development (HRD) activities have expanded. Informed by an institutional theory perspective, we examined the evolution of HRD as well as HRD-related programs in ASEAN to illuminate the mechanisms and conditions shaping HRD in ASEAN. Our primary sources were archival data from ASEAN from 1967–2021 and relevant publications of international development agencies that feature HRD-related activities in the region. Our analysis suggests that the establishment of an intergovernmental organization (i.e., ASEAN), with its continuing efforts towards economic cooperation and community building among its member states, was central to the emergence and development of Regional HRD in Southeast Asia. This inquiry advances understanding of the role of intergovernmental institutions in influencing HRD activities. The study also showcases the critical role of HRD in furthering common interests around economic and socio-cultural initiatives in ASEAN.